Recent advances in polyhydroxyalkanoate production from volatile fatty acids derived from food waste fermentation - Tao, Xue; Liu, Shiqi; Lv, Longyi; Sun, Li; Zhang, Guangming; Liang, Jinsong; Zou, Wenxiu (Frontiers in Microbiology, 2025)
Polyhydroxyalkanoates (PHAs) are promising green substitutes for traditional plastics, offering good biodegradability and biocompatibility. PHA production using volatile fatty acids (VFAs) obtained from food waste fermentation not only provides a new way to utilize food waste resources but also reduces the PHA production cost. However, a review of mechanisms, technical processes, key influencing factors, and techno-economic analysis of food waste-VFAs-PHA production is lacking. Thus, this review elucidates the microorganisms that synthesize PHA and their associated metabolic pathways. A technical process of food waste-VFAs-PHA generation was proposed. Research status in this field was summarized. Meanwhile, the influencing factors of PHA synthesis based on VFAs were discussed. Additionally, techno-economic and environmental analyses of the food waste-VFAs-PHA process were covered. Finally, the challenges and prospects of future work were proposed. This review provides new ideas and theoretical guidance for achieving industrial production of low-cost PHA and the value-added transformation of food waste.